Pulmonary embolism in COVID-19 - V. Ilyina-Stohniienko; Yu. Kharchenko; A. Zaretska; A. Savchuk; A. Kolotvin (Kazimierz Wielki University, 2022)
COVID-19 pandemic is recognized as a present day major public health burden. Risk factors for developing a more severe course of COVID-19 include increased levels of C-reactive protein and D-dimer. Pulmonary embolism (PE) is challenging in patients with COVID-19. The purpose: to analyze clinical and paraclinical manifestations of PE in patients with COVID-19 in order to develop a system for its early diagnosis, prediction of complications, prevention and treatment. 52 patients aged 28 - 81 y.o. with a diagnosis "Acute respiratory disease COVID-19" have been examined during 2020-2021. (98.08±1.9)% of PE patients had a history of one or more comorbidities, including obesity (80.77%), coronary heart disease (96.15%), hypertension (98.08%), peripheral arteries (92.3%), type 2 diabetes mellitus (48.08%). Evaluation of laboratory parameters revealed increasing lymphocytopenia, leukocytosis, neutrophilia, thrombocytopenia (p<0.05). Biochemical parameters showed high CRP, increase in creatinine, decrease in glomerular filtration rate (p<0.05). A direct relationship was found between overweight and an increase in the content of C-RP in COVID-19 and PE patients. Conclusions: age over 65, hypertension and obesity are risk factors for severe course of COVID-19 and PE.